The Effectiveness of Using Video on Students’ Writing Ability in Teaching Descriptive Text (A Case Study At Tenth Grade Of Smk Pasundan 1 Kota Serang) - Ita Miftahussaidah Rivai; Early Amalia Arniz; Sibghatullah Mujadidi (English Department - University of Sultan Ageng Tirtayasa, 2017)
The purpose of the study was to know the empirical evidence about the effect of using video on students’ writing ability in descriptive text. In this research, the writer conducts a quasi-experimental research with nonequivalent control group pretest-posttest design. In the nonequivalent control group pretest-posttest design, the dependent variable is measured both before and after treatment or intervention. In the research used two instruments which are used for gathered the data that the researcher needs; they are; pre-test and post-test as the research instruments to collect the data. Test is used in order to know the difference achievement between experiment class and controlled class after the treatment was given. The method in this study was a quantitative method. The writer used formula to analyze the effect using video in teaching and to take the data. The data required are the curriculum used by the school, the information of the English teaching learning activity condition, the books are used in the teaching learning activity, and the students’ test answers on writing skill given by the writer as the researcher. The result of the research showed that the value of t˳ is higher than tt, so the Research Hypothesis (H) is accepted and the Null Hypothesis (H˳) is rejected. Based on the result above, it can be concluded that the effect of video on students’ writing ability in descriptive text. Thus, it means that the learning writing descriptive using video was successful in improving students’ ability. Keywords : Descriptive text, writing skill, Video